Discrete mathematics, 6th edition - Johnsonbaugh Richard (Dorling kindsley, Delhi, 2007)
Stats/Maths
UGC XIth Five Year Plan 2009-2010
ENGLISH
Keywords: Discrete mathematics, 6th edition; Stats/Maths; Stats/Maths